2017
DOI: 10.1017/jfm.2017.485
|View full text |Cite
|
Sign up to set email alerts
|

Consistent formulations for stability of fluid flow through deformable channels and tubes

Abstract: In the formulation of stability of fluid flow through channels and tubes with deformable walls, while the fluid is naturally treated in an Eulerian framework, the solid can be treated either in a Lagrangian or Eulerian framework. A consistent formulation, then, should yield results that are independent of the chosen framework. Previous studies have demonstrated this consistency for the stability of plane Couette flow past a deformable solid layer modelled as a neo-Hookean solid, in the creeping-flow limit. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…Similarly, the Lagrangian formulation of Chokshi and Kumaran 9 was inconsistent because the base quantities were left as a function of the undeformed coordinates instead of pre-stressed state coordinates as dictated by the momentum balance equation for the perturbed state. The above inconsistencies were resolved recently by Patne et al 10 who proposed consistent Eulerian and Lagrangian formulations for the solid which is used in the present study.…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, the Lagrangian formulation of Chokshi and Kumaran 9 was inconsistent because the base quantities were left as a function of the undeformed coordinates instead of pre-stressed state coordinates as dictated by the momentum balance equation for the perturbed state. The above inconsistencies were resolved recently by Patne et al 10 who proposed consistent Eulerian and Lagrangian formulations for the solid which is used in the present study.…”
Section: Introductionmentioning
confidence: 79%
“…Taylor expanded Direction of Taylor expansion Instabilities Gkanis and Kumar [10] fluid and solid normal FW and SW Gaurav and Shankar [11] fluid normal SW, low-Re, WM, and IM Patne et al [12] fluid tangential and normal SW, WM, and IM of plane Poiseuille flow of a Bingham fluid with a rigid plug was first studied by Frigaard et al [2]. They predicted that the minimum Reynolds number for linear instability increases almost linearly with increasing Bingham number.…”
Section: Workmentioning
confidence: 99%
“…Later, Patne et al [12] demonstrated that a consistent way to derive the interface conditions is to Taylor expand fluid base-state quantities in both flow and normal directions provided that the solid and fluid are described in the Lagrangian and Eulerian frameworks, respectively. The aforementioned Taylor expansion gave rise to a term in normal stress balance at the fluid-solid interface which resulted in an interaction between the base-state pressure gradient and perturbations.…”
Section: Workmentioning
confidence: 99%
See 2 more Smart Citations